Combined basic therapy of rheumatoid arthritis with methotrexate and plaquenil - N A Sergiets; N K Erov; N A Sergiets; N K Erov (Терапевтический архив, 2009)
Aim. To compare efficacy of basic RA treatment with methotrexate+plaquenil and basic monotherapy with methotrexate. Material and methods. Two groups of rheumatoid arthritis (RA) patients were studied: group 1 (n = 82) received combined basic treatment with methotrexate (7.5 mg/week) in combination with plaquenil (0.2 ?mg/day); group 2 (n = 60) received methotrexate monotherapy according to the same scheme; all the patients received also diclofenak in a dose 100 mg/day; low-dose glucocorticosteroids were given to 36 and 24 patients, respectively. To improve methotrexate tolerance, all the patients took folic acid (1-2 mg/day 5 days a week). Efficacy of the treatment was evaluated by regression and final value of inflammation activity. Results. 6-month treatment produced in groups 1 and 2 good effect in 27.6 and 21.4%, satisfactory effect - in 65.5 and 66.6% patients, respectively. No effect was seen in 6.8 and 11.9% patients, respectively. A good effect was achieved in group 1 in 73.3 ± 5.4 days; in group 2 - in 93.7 ± 5.9 days (p < 0.05). In 12 months good and satisfactory effects persisted. Side effects occurred with the same frequency in both groups primarily in those who did not take folic acid. Conclusion. Combined basic therapy of RA with methotrexate and plaquenil was more effective than monotherapy with methotrexate because it produced good effects more frequently and earlier while no response was seen less often.